2011
DOI: 10.1016/j.cam.2011.01.047
|View full text |Cite
|
Sign up to set email alerts
|

An almost fourth order uniformly convergent domain decomposition method for a coupled system of singularly perturbed reaction–diffusion equations

Abstract: a b s t r a c tWe consider a system of M(≥ 2) singularly perturbed equations of reaction-diffusion type coupled through the reaction term. A high order Schwarz domain decomposition method is developed to solve the system numerically. The method splits the original domain into three overlapping subdomains. On two boundary layer subdomains we use a compact fourth order difference scheme on a uniform mesh while on the interior subdomain we use a hybrid scheme on a uniform mesh. We prove that the method is almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The extended cubic B-spline is considered in [15]. A domain decomposition method is considered in [16,17]. The authors in [18,19] proposed hybrid scheme on both Shishkin and Bakhvalov meshes.…”
Section: Introductionmentioning
confidence: 99%
“…The extended cubic B-spline is considered in [15]. A domain decomposition method is considered in [16,17]. The authors in [18,19] proposed hybrid scheme on both Shishkin and Bakhvalov meshes.…”
Section: Introductionmentioning
confidence: 99%
“…In [20], an analysis of overlapping domain decomposition methods for singularly perturbed reaction-diffusion problems with distinct small positive parameters is presented. The authors of [20] found a flaw in the analysis of domain decomposition methods explored in [6,13,18]. The authors observation is that the constant C is not independent of the iteration number k and it is growing at each induction step in their proof of [6,13,18].…”
mentioning
confidence: 99%
“…The authors of [20] found a flaw in the analysis of domain decomposition methods explored in [6,13,18]. The authors observation is that the constant C is not independent of the iteration number k and it is growing at each induction step in their proof of [6,13,18]. But in [20] the authors have presented an alternate analysis of overlapping domain decomposition methods for singularly perturbed reaction-diffusion problems with two parameters and problems in [18].…”
mentioning
confidence: 99%